Pertumbuhan Bibit Hopea mengarawan Miq. Pada Intensitas Cahaya Berbeda - Elfans Bawalsyah S.A.; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2015)
An experimental study on growth of Hopea mengarawan Miq. seedlings under different light intensity was conducted from June to October 2012 at open field. This experiment aimed to find out optimal light intensity for the growth of H. mengarawan seedlings. The study used completely randomized design with four treatments and six replications. The treatments were control (100), 80, 60 and 40% of light intensities. The result showed light intensity did not give significant effect to the growth of H. mengarawan seedlings.